APLIKASI STUDI KELAYAKAN USAHA BERBASIS NPV DAN PAYBACK PERIOD DALAM MENGANALISIS USAHA KAFE KOPI FILTER - Andreas Kiky (Jurnal Bina Manajemen, 2020)
Coffee Industry has been grown since 1980. Recently coffee industry entered 3rd wave coffee generation which elaborate more on the taste of the coffee. Most of 3rd wave coffee products focus on user experience on unique flavor of the coffee beans. Coffee has become a craft beverage and life style for the consumer. Base on this new trend then new concept of coffee café are growing in 2015. Many business owner and young generation start their coffee café business base on the following trend. In Indonesia, there are a lot of coffee café that offer 3rd wave product along with 2nd wave coffee products. Based on financial approach, NPV and payback period are the most common methods to address business feasibilities in long run. However, what is usually miss by financial method is entrepreneurial spirit and also several “factors” that cannot be expressed in numerical value. This research has a goal to applied financial theory in real world study. The result from thisresearch is only forecasting based on untested assumption and still lack of accuracyand open for further improvement.